Alokasi Waktu Wanita Pada Industri Kerajinan Anyaman Pandan Di Kota Sungai Penuh - Suandi Suandi; Yusma Damayanti; Jasminarni Jasminarni; Trias Novita (Indonesian Journal of Cultural and Community Development, 2018)
This research aims at examining how women allocate their time of working in pandanus handicraft industry on Sungai Penuh City and to analyze affect women's time allocation in pandanus craft industry. The study was conducted in Kota Dian Village Hamparan Rawang District Sungai Penuh City. This study employed cross-section primary data. The data collection was conducted from June until October 2017 by interviewing 32 womens who were selected by cluster and purposive sampling. Data were tested by descriptive and multiple regression test. The results showed that the average time allocation of women in pandanus industry for 30 hours / week or 5 hours /day by working part-time. Women has dual-role in the household. From the regression analysis, two significant factors observed. These are the number of household members and the earnings of the household, while the age factor and level of education of women have no significant effect.